The Tuvaaluk and Torngat archaeological projects: Review and assessment - Fitzhugh, William (Études/Inuit/Studies, 2015)
In the late 1970s, two large, multi-disciplinary, multi-year archaeological programs were initiated along the coasts of northern Labrador and Ungava in northern Quebec. Both envisioned a new model for Arctic archaeology that integrated archaeology, ethnography, environmental studies, earth sciences, and informatics. The Tuvaaluk research program was directed by Patrick Plumet at the Université du Québec à Montréal, and the Torngat Archaeological Project (TAP) by William Fitzhugh at the Smithsonian Institution and Richard Jordan at Bryn Mawr College. Project periods lasted roughly five years and included researchers and students from several institutions. The Tuvaaluk project concentrated on Paleoeskimo and Thule cultures, while TAP included research on Maritime Archaic and later Indian cultures as well as Paleoeskimo and Inuit cultures. This paper reviews and compares Tuvaaluk and TAP goals, methods, results, lessons learned, and legacies.